2014
DOI: 10.1136/postgradmedj-2013-132474
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulants: integration into clinical practice

Abstract: The introduction of direct oral anticoagulants (OACs) for the treatment and prevention of thromboembolic disease represents a shift from the traditional vitamin K antagonist-based therapies, which have been the mainstay of treatment for almost 60 years. A challenge for hospital formularies will be to manage the use of direct OACs from hospital to outpatient settings. Three direct OACs—apixaban, dabigatran and rivaroxaban—are widely approved across different indications, with rivaroxaban approved across the wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…In adult studies, NOACs have been demonstrated to be efficacious and in the United States are approved for the use in stroke prevention from atrial fibrillation, the treatment of acute deep vein thrombosis (DVT), secondary prevention of DVT, DVT prevention post elective knee and hip surgery (80), and in the treatment of acute pulmonary embolus (81,82).…”
Section: Novel Oral Anticoagulantsmentioning
confidence: 99%
“…In adult studies, NOACs have been demonstrated to be efficacious and in the United States are approved for the use in stroke prevention from atrial fibrillation, the treatment of acute deep vein thrombosis (DVT), secondary prevention of DVT, DVT prevention post elective knee and hip surgery (80), and in the treatment of acute pulmonary embolus (81,82).…”
Section: Novel Oral Anticoagulantsmentioning
confidence: 99%
“…Edoxaban elimination is only slightly dependent on CYP3A4 mechanisms and is mostly mediated by P-gp. 16 Dabigatran is dependent on P-gp …”
Section: Interactionsmentioning
confidence: 99%
“…In fact, after major elective orthopedic surgery the incidence of a VTE is estimated to be 40% -60% if anticoagulant therapy is not applied. 1 Conditions such as cardiac arrhythmias also require anticoagulant intervention. Atrial fibrillation (AF) is the most common cardiac arrhythmia.…”
mentioning
confidence: 99%
“…For this reason they require constant monitoring and dose adjustments. 1 The disadvantage of parenteral agents is their expense and their inability to be given orally. This prevents them from being a long term solution, however because they act quickly they can be used as an anticoagulant bridge until the slower acting VKA can take effect.…”
mentioning
confidence: 99%